RELASI BUDAYA DALAM PENYEBARAN ISLAM DI BUMI WALI TUBAN - Jamal Ghofir (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2018)
Tuban As a coastal area has become an important area for all the development of the archipelago's culture. This is partly due to the location of Tuban as a large port in the northern coastal area which is the main route for the entry of all outside cultures in the interior. So that the process of the spread of culture, especially Islam (Middle East), is in Indonesia, so the city of Tuban becomes important to study as the location of the beginning of the cultural scene.